Reversing the biofilm-inducing effect of two xanthones from Garcinia mangostana by 3-methyl-2(5H)-furanone and N-butyryl-D-L homoserine lactone (2023)
ABSTRACT: Background: According to the WHO, 12 bacteria cause numerous human infections, including Enterobacteriaceae Klebsiella pneumoniae, and thus represent a public health problem. Microbial resistance is associated with biofilm formation; therefore, it is critical to know the biofilm-inducing potential of various compounds of everyday life. Likewise, the reversibility of biofilms and the modulation of persister cells are important for controlling microbial pathogens. In this work, we investigated the biofilm-inducing effects of xanthones from Garcinia mangostana on Klebsiella pneumoniae. Furthermore, we investigated the reversal effect of 3-methyl-2(5H)-furanone and the formation of persister cells induced by xanthones and their role in modulating the biofilm to the antibiotic gentamicin. Methods: To analyze the biofilm-inducing role of xanthones from Garcinia mangostana, cultures of K. pneumoniae containing duodenal probe pieces were treated with 0.1–0.001 μM α- and γ-mangostin, and the biofilm levels were measured using spectrophotometry. To determine biofilm reversion, cultures treated with xanthones, or gentamicin were mixed with 3-methyl-2(5H)-furanone or N-butyryl-DL-homoserine lactone. The presence of K. pneumoniae persister cells was determined by applying the compounds to the mature biofilm, and the number of colony-forming units was counted. Results: The xanthones α- and γ-mangostin increased K. pneumoniae biofilm production by 40% with duodenal probes. However, 3-methyl-2(5H)-furanone at 0.001 μМ reversed biofilm formation by up to 60%. Moreover, adding the same to a culture treated with gentamicin reduced the biofilm by 80.5%. This effect was highlighted when 3-methyl-2(5H)-furanone was administered 6 h later than xanthones. At high concentrations of α-mangostin, persister K. pneumoniae cells in the biofilm were about 5 – 10 times more abundant than cells, whereas, with γ-mangostin, they were about 100 times more. Conclusion: Two xanthones, α- and γ-mangostin from G. mangostana, induced biofilm formation in K. pneumoniae and promoted persister cells. However, the biofilm formation was reversed by adding 3-methyl-2(5H)-furanone, and even this effect was achieved with gentamicin. In addition, this compound controlled the persister K. pneumoniae cells promoted by α-mangostin. Thus, synthetic, and natural biofilm-inducing compounds could harm human health. Therefore, avoiding these substances and looking for biofilm inhibitors would be a strategy to overcome microbial resistance and recover antibiotics that are no longer used.